1998
DOI: 10.1007/bf03182514
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis and accuracy of PIV data

Abstract: In an assessment of PIV measurement accuracy under practical experimental circumstances, grid-generated turbulence in its early decay (xiM =13.6-15.2, ReA z 25) has been studied. Since a realtime processor was used, it was practical to acquire a statistically significant sample size of 3000 vector maps so that accurate turbulence statistics could be calculated. Results include moments of velocity components and spatial structures in terms of auto-correlations, turbulence scales and spectra. Data fall within li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…The uncertainty in the ensemble average PIV data describing turbulent flows is mainly dependent on the sample size and the order of statistics. Ullum et al [98] investigated the effect of sample size on the accuracy of time-averaged PIV data for a single point in a grid-generated turbulence in its early decay. It was concluded that 100 vector maps for a component of mean velocity were required for an uncertainties of averages at a given point to be within 1% for a flow of 10% turbulence intensity.…”
Section: Discussionmentioning
confidence: 99%
“…The uncertainty in the ensemble average PIV data describing turbulent flows is mainly dependent on the sample size and the order of statistics. Ullum et al [98] investigated the effect of sample size on the accuracy of time-averaged PIV data for a single point in a grid-generated turbulence in its early decay. It was concluded that 100 vector maps for a component of mean velocity were required for an uncertainties of averages at a given point to be within 1% for a flow of 10% turbulence intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Uzol and Camci 46 and Ullum et al 47 Six random locations in the field of view, indicated in Figure 7, were selected as samples and their stream-wise velocity component compared.…”
Section: Particle Image Velocimetry (Piv)mentioning
confidence: 99%
“…Originally used to obtain two-dimensional velocity fields, developments over the last decade have led to the successful realization of three-dimensional velocity fields (Lynch and Thurow, 2011). Statistical properties of the mean and turbulent components can be estimated from ensemble averaging (Ullum et al, 1998). However, accuracy of the statistical analysis depends on the sample size over which the ensemble averages are formed (Uzol and Camci, 2001).…”
Section: Experimental Setup and Statistical Analysis Of Piv Datamentioning
confidence: 99%